Tricyclic Pyrazoles: An Efficient Approach to Cannabinoid Analogues with a Tricyclic Framework Incorporating the Pyrrole and Pyrazole Moieties - Pinna, Giansalvo; Pinna, Gérard A.; Chelucci, Giorgio; Baldino, Salvatore (Synthesis, 2012)
In this paper we report the synthesis of some new cannabinoid analogues that share with rimonabant, a potent and selective CB1 antagonist, the 2,4-dichlorophenyl and piperidin-1-yl substituents on the pyrazole and amide nitrogens, respectively. The general synthesis involves the preparation of a cyclic ketone condensed with a pyrrole, followed by Claisen condensation with diethyl oxalate; from here, an aza-annulation reaction with a substituted hydrazine followed by an amidation step complete the synthesis.
Keywords: cannabinoids; tricyclic pyrazoles; Friedel–Crafts acylation; Claisen condensation; aza-annulation